Association of P16 Expression with Clinicopathological Features of Oral Cavity Squamous Cell Carcinoma Patients in Bali - Ampur, O. Y.; Sudarsa, I Wayan; Suryawisesa, Ida Bagus (BALI MEDICAL JOURNAL, 2016)
Background: Oral cavity cancer is considered as a major health problem worldwide and has been associated with high recurrence rate and poor prognosis. Oral cavity squamous cell carcinoma (OCSCC) in Sanglah General Hospital Denpasar contributed to 71.7% of all head and neck cancer from 2002-2011 with an increasing trend annually. Advances in our understanding of OCSCC have not improved the outcome in OCSCC management significantly. Therefore, many studies have focused on the roles of biomolecular markers in OCSCC. One of biomolecular marker that has been the focus of many OCSCC studies is p16. Method: This was an analytic cross sectional study with 31 samples to determine the association of p16 expression with age group, tumor location, stage, and grade in OCSCC. Data was analyzed descriptively and the association between variables were evaluated with Chi-Square or Fisher’s Exact Test with a p value